Investigasi Kualitatif pada Faktor-faktor yang Mendorong Minat Masyarakat terhadap Penggunaan Bank Syariah di Indonesia: A Qualitative Investigation of the Factors Driving Public Interest in the Use of Sharia Bank in Indonesia - Rizka Nabilah Al-Wakhidah; Muhammad Yazid (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
Islamic banking is present as a solution to the conventional banking system, by offering products that are in accordance with Islamic principles, Islamic banking has succesfully developed in Indonesia. This research aims to identify the factors that drive people’s interest in using the products. Using a qualitative approach, this study collected data trhough interviews with informants who have experience or interest in Islamic banking products. The results show that the factors that influence people’s interest in using Islamic bank products and services are driven by the awareness of halal principles and the concept of usury, people are also very satisfied with the administrative costs wich are considered lower than the administration of conventional banks. In addition, the variety of Islamic bank products has also succeesed in attracking public attention. This has a positive impact on the national economy. However, the level of public understanding of these products still needs to be improved. Some complex Islamic products are often insufficiently understood by the general public, therefore, more intensive education is needed tp maximize the utilization of sharia financial products.